Human Self Structure in Islamic Psychology: Human Self Structure in Islamic Psychology - Abdul Rahman (Da'wa Faculty of Islamic State University Salatiga, 2025)
In Islamic psychology, the study of the human self refers to a deep understanding of human nature and essence as explained in the Quran. Terms such as al-ins, al-basyar, al-qalb, and al-aql play an important role in understanding this concept. Al-ins and al-basyar are often used to describe humans in general. Al-basyar emphasizes the physical and biological aspects of human beings, reflecting humanity in its visible physical form. In contrast, al-ins more often refer to humans in both social and spiritual contexts. Al-qalb (heart) in the Qur'an goes beyond the physical sense, encompassing the spiritual and emotional center of man. In Surah Al-Hajj (22:46), it is stated that blindness refers to the blindness of the heart, not the eyes. Al-aql (intellect) refers to intellectual capacity and the ability to think rationally. Reason is a tool for acquiring knowledge and achieving a deep understanding of life and existence.